Power in religious discourse: a discourse analysis of two sermons from the Universal Church of the Kingdom of God - Cipriani, Andréia Cristina (2002)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão. Programa de Pós-Graduação em Letras/Inglês e Literatura Correspondente.